El Papa Juan Pablo II - Centro de Estudios Teológicos de la Amazonía (CETA) (My University, 1900)
SPANISH: El Papa Juan Pablo II de pie frente a los presentes cuando da su mensaje al pueblo de Iquitos, también se puede ver al Padre Jaoquín García de espaldas.
ENGLISH: Pope John Paul II standing in front of those present when he gives his message to the people of Iquitos, Father Jaoquin Garcia can also be seen with his back turned.

SPANISH: El Papa Juan Pablo II de pie frente a los presentes cuando da su mensaje al pueblo de Iquitos, también se puede ver al Padre Jaoquín García de espaldas.
ENGLISH: Pope John Paul II standing in front of those present when he gives his message to the people of Iquitos, Father Jaoquin Garcia can also be seen with his back turned.
Pope John Paul II
Keywords: Iquitos (Perú)|~|Actividades culturales|~|Perú|~|Perú--Cultura Amazónica|~|Perú--Personajes Religiosos